Cadherins mediate sequential roles through a hierarchy of mechanisms in the developing mammillary body - Szabó, Nora-Emöke; Haddad-Tóvolli, Roberta; Zhou, Xunlei; Alvarez-Bolado, Gonzalo (Frontiers in Neuroanatomy, 2015)
Expression of intricate combinations of cadherins (a family of adhesive membrane proteins) is common in the developing central nervous system. On this basis, a combinatorial cadherin code has long been proposed to underlie neuronal sorting and to be ultimately responsible for the layers, columns and nuclei of the brain. However, experimental proof of this particular function of cadherins has proven difficult to obtain and the question is still not clear. Alternatively, non-specific, non-combinatorial, purely quantitative adhesive differentials have been proposed to explain neuronal sorting in the brain. Do cadherin combinations underlie brain cytoarchitecture? We approached this question using as model a well-defined forebrain nucleus, the mammillary body (MBO), which shows strong, homogeneous expression of one single cadherin (Cdh11) and patterned, combinatorial expression of Cdh6, −8 and −10. We found that, besides the known combinatorial Cdh pattern, MBO cells are organized into a second, non-overlapping pattern grouping neurons with the same date of neurogenesis. We report that, in the Foxb1 mouse mutant, Cdh11 expression fails to be maintained during MBO development. This disrupted the combination-based as well as the birthdate-based sorting in the mutant MBO. In utero RNA interference (RNAi) experiments knocking down Cdh11 in MBO-fated migrating neurons at one specific age showed that Cdh11 expression is required for chronological entrance in the MBO. Our results suggest that neuronal sorting in the developing MBO is caused by adhesion-based, non-combinatorial mechanisms that keep neurons sorted according to birthdate information (possibly matching them to target neurons chronologically sorted in the same manner). Non-specific adhesion mechanisms would also prevent cadherin combinations from altering the birthdate-based sorting. Cadherin combinations would presumably act later to support specific synaptogenesis through specific axonal fasciculation and final target recognition.